Stages of communication in children with autism - Troshanska, Jasmina; Trajkovski, Vladimir (Faculty of Philosophy, UKIM, Skopje, Macedonia, 2014)
Introduction: communication is an activity of transfer and exchange of thoughts, messages or information by speech, visualization, signals, writing or behavior. According to the definition of de Valenzuela, communication is “an act by which a person gives or receives information for another person’s needs, desires, perceptions, knowledge or affective states”. Problems in communication, as defined, in children with autism depend proportionally on their intellectual and social development. The skills of communication have their own developmental course, where there are stages of development: pre-intentional reflex communication, pre-intentional reactive communication, pre-intentional proactive communication, intentional primitive communication and stage of intentional verbal communication. The purpose of this paper is to present the behavior of children with autism who are in different developmental stages of communication. The objective of the paper is an analysis of the behavior of an autistic child who is in a stage: pre-intentional reflex communication, pre-intentional reactive communication, pre-intentional proactive communication; intentional primitive communication and analysis of the behavior of a child with autism in the stage of intentional verbal communication. The research will be based on qualitative data obtained through researching the the literature in English language and through the use of Internet sources. The data will be systematized and presented in tables. Conclusion: the level of development and progress of the child with autism, the acquisition of new concepts, skills and abilities depends on successful communication. In the daily contact and work with children with autism, it is necessary to estimate the stage of communication of the child for further development of communication and social skills, through planning the content and activities for individual and group work. Based on the developmental level of the child, today there are possibilities to use a number of alternative and augmentative communication tools such as computer programs, images, signs, symbols, etc.
Fourth International Conference: Modern Aspects of Special Education and Rehabilitation of Persons with Disabilities, 2013 October 17-19; Ohrid.
Keywords: autism, communication, children